2006
DOI: 10.1212/01.wnl.0000238179.79888.44
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of rizatriptan in migraine attacks in children

Abstract: Oral rizatriptan is effective and well-tolerated for migraine attacks in children over age 6 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 19 publications
3
61
0
2
Order By: Relevance
“…5,8 Despite this, studies in adults have shown triptans to be effective as abortive therapy in the ED setting, 25 but there have not been any ED-based pediatric studies. The evidence for pediatric use of triptans in the outpatient setting is strong, [26][27][28][29] yet only 3% of children received a triptan in the current study.…”
Section: Discussionmentioning
confidence: 67%
“…5,8 Despite this, studies in adults have shown triptans to be effective as abortive therapy in the ED setting, 25 but there have not been any ED-based pediatric studies. The evidence for pediatric use of triptans in the outpatient setting is strong, [26][27][28][29] yet only 3% of children received a triptan in the current study.…”
Section: Discussionmentioning
confidence: 67%
“…50 Rizatriptan (5 mg for body weight 20-39 kg, 10 mg >40 kg) has also been evaluated in 96 young patients aged 6-17 years in a double-blind, placebo-controlled, cross-over trial. 51 Patients receiving either dose of rizatriptan achieved headache relief by two grades at 2 hours compared with placebo (p<0.001). Rizatriptan was superior at 3 and 4 hours and was consistent over two treated attacks.…”
Section: Rizatriptanmentioning
confidence: 97%
“…Studies uniformly showed high efficacy and safety, but mostly failed to show advantage over placebo with 2 exceptions [Ahonen et al, 2004[Ahonen et al, , 2006.…”
Section: Triptan Trials In Children and Adolescentsmentioning
confidence: 99%
“…* Sumatriptan NS [Ueberall et al, 1999], N 5 14, 85% * Sumatriptan NS [Ahonen et al, 2004], N 5 83, 69% * Sumatriptan NS [Winner et al,2000], N 5 510, 63% * Sumatriptan PO [Hamalainen et al, 1997], N 5 23, 30% * Sumatriptan PO [Winner et al, 1997], N 5 302, Unstated * Naratriptan PO [Rothner et al, 1997], N 5 300, 72% * Rizatriptan PO [Winner et al, 2002], N 5 296, 66% * Rizatriptan PO [Ahonen et al, 2006], N 5 96, 74%…”
Section: Triptan Trials In Children and Adolescentsmentioning
confidence: 99%